Sex, gender and rights: from the “right to sexual orientation and gender identity” to the “right to self-determination of gender - Martínez de Pisón Cavero, José (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
Since the beginning of the 21st century, sexual orientation and gender identity have been recognized as rights of the LGBTIQ collective by reports from organizations, international documents on human rights and by court decisions. These rights are intended to prevent discrimination against these people, the prohibition of violence and hatred and the full enjoyment of fundamental rights and freedoms. However, there are still groups of people, such as intersex, transgender, queer, non-binary, etc., who do not feel identified with the formulation of this right. This article analyzes the different aspects of this debate and explores the way to justify a right to self-determination of sex.